2011
DOI: 10.1002/masy.201000142
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Gelation Behaviour of Double Responsive P2VP‐b‐PEO‐b‐P(GME‐co‐EGE) Triblock Terpolymers: A SANS Study

Abstract: Summary: Aqueous solutions of a double responsive P2VP 62 -b-PEO 452 -b-P(GME 36 -co-EGE 36 ) triblock terpolymer were investigated by means of small-angle neutron scattering (SANS) in order to derive information about structural changes going along with the temperature triggered gel-sol-gel transition at pH ¼ 7, and the sol-gel transition at pH ¼ 3.5, respectively, observed by rheology. SANS measurements on dilute samples at different pH and temperature confirmed the formation of core-shell-corona micelles un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Thermoresponsive triblock terpolymers have gained a lot of interest because they have fascinating self-assembly behaviour and form micelles with complex structures like core-shell micelles. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Furthermore at the right concentration and temperature they form multicompartment injectable gels. 36,39,[43][44][45][46][47][48][49][50] The gel formation has been shown to be affected by many parameters like the MW, composition, block length, chemistry of the polymer as well as the polymer architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoresponsive triblock terpolymers have gained a lot of interest because they have fascinating self-assembly behaviour and form micelles with complex structures like core-shell micelles. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Furthermore at the right concentration and temperature they form multicompartment injectable gels. 36,39,[43][44][45][46][47][48][49][50] The gel formation has been shown to be affected by many parameters like the MW, composition, block length, chemistry of the polymer as well as the polymer architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Schmalz and co-workers investigated the temperature-dependent gelation behavior of double responsive P2VP 62 - b -PEG 452 - b -P­(GME 36 - co -EGE 36 ) terpolymers, while the 2VP units introduced pH responsivity. Hydrogel formation was observed, if one of the end blocks was insoluble and further showed a temperature-induced gel–sol–gel transition. , These block copolymers were part of a review by Manners and co-workers in 2012, presenting functional block copolymers utilized as nanostructured materials . In 2014, Kamata et al demonstrated the synthesis of “nonswellable” hydrogels without mechanical hysteresis, capitalizing on star-shaped four-arm P­(GME- co -EGE) copolymers .…”
Section: Bioapplication Of Thermoresponsive P(scage)smentioning
confidence: 99%
“…In 2011, Schmalz and co-workers synthesized ABC block copolymers by the use of phosphazene bases, incorporating a copolymer block consisting of GME and EGE. 75 In contrast to classic AROP of epoxides where the oxyanion and lithium form strong ionic aggregates, 16 catalysis by phosphazene bases enables polymerization despite the presence of lithium counterions. During the reaction, the phosphazene base forms a [Li-tBuP 4 ] + complex while suppressing ion pair association of the lithium alkoxide.…”
Section: ■ Polymerization Of Scagesmentioning
confidence: 99%
See 1 more Smart Citation